The application potential of SiO2, TiO2 or Ag nanoparticles as fillers in machining process fluids. (20th January 2017) - Bakalova, Totka; Svobodová, Lucie; Rosická, Petra; Borůvková, Karolína; Voleský, Lukáš; Louda, Petr
Abstract: Process fluids are important as they create the appropriate conditions for machine cutting by improving heat transfer, whereby extending the life of the cutting tool and increasing the surface quality of the product. The use of nanoadditives in the form of nanoparticles is highly efficient due to their high chemical and biological activity. Nanoparticles dispersed in a volume of process fluid can easily penetrate between friction surfaces and thereby greatly influence the elastohydrodynamic effect of the lubrication. In our experiment, the addition of nanoparticles has a positive effect on reducing the average of friction coefficient during the tribological process by 8.9% and reducing the variance of friction coefficient by 20.4%, as they lead to faster stabilization resulting in a significant reduction in the depth of material being removed by up to 52.1%. In this paper, the antibacterial properties of process fluids with nanoparticles of TiO2, SiO2 or Ag were also evaluated (respiratory rates and bacterial viability). The results indicated that the nanoparticles reduced bacterial respiratory rates and viability by up to 90.4%. Graphical abstract: Highlights: SiO2, TiO2 and Ag nanoparticles can serve as fillers in machining process fluids. Nanoparticles inhibit bacterial growth (respiratory and viability) by up to 90.4%. Nanoparticles reduce the average of friction coefficient by up to 8.9%. Nanoparticles reduce the variance of friction coefficient by 20.4%. Nanoparticles reduce the depth of material being removed by up to 52.1%.